SHORT TERM ACTIVITY ADAPTATION DECISION OF MOBILE PROFESSIONAL: GENDER DIFFERENCES ON TRAVEL IMPACT OF SMART PHONE ADOPTION - Christin, Gloriani Novita; Tamin, Ofyar Z.; Santosa, Idwan; Miharja, Miming (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Understanding individual travel behaviour in urban space is essential for transportation planning. Considering that most of travel is a derived demand from the need to engage in activities, hence predicting individual responses, particularly gender role on short term activity adaptation decision is effective in understanding the relationship between travel behaviour and daily activity. In the information era, widespread adoption of smartphones, which is the result of convergence of Information and Communication Technology, potentially influences activities of mobile professionals. They use smart phone as a tool to improve the productivity and to assure the efficiency of their “travelling” as a part of their daily mobile work. Result of survey, which consists of interviews and simulation using stated adaptation in the Greater Jakarta Area provides basic pattern of response by gender that occur when information was received during implementation of activities. The proposed rule is a potentially valuable concept to predict changes in planned activity schedules as a function of unexpected event.